THE EFFECTIVENESS OF USING TEAM WORD-WEBBING IN TEACHING LITERAL READING COMPREHENSION AT THE TENTH GRADE OF SMA NEGERI 15 PANGKEP - Asmira Suryaningsih; Nurdevi Bte Abdul; Uyunnasirah Hambali (English Language Teaching Methodology, 2021)
The principle target of this examination was to decide the adequacy of the effectiveness of using the Team Word-webbing in learning reading comprehension which comprises of increasing literal reading comprehension (in the term of main idea and in the term supporting details). The information was gotten by utilized pre-test and post-test plan. The count results show that the utilization of Team Word Webbing can improve reading comprehension skills of students. The students reading comprehension skills utilizing Team Word Webbing indicated preferred learning results over before the usage of Team Word-webbing. The aftereffects of factual examination utilizing the t-test recipe, the specialist acquired a t-value was 4.697 with a recurrence of df = 25-1 = 24, at the 50% essentialness level got t-table was 2.640. So the t test> t table or the invalid theory (H0) was dismissed and the elective speculation (H1) was acknowledged. Utilizing Team Word Webbing was entirely pleasant in the learning cycle and can help understudies increment their reading comprehension skills.